A study of correlation between macular ischaemia and diabetic nephropathy in diabetes mellitus - Shrikant Deshpande; Priyanka Karande (Al Ameen Medical College, 2022)
Introduction: Some studies have reported an association between ischaemia of the macula as seen on fundus fluorescein angiography (FFA) with diabetic nephropathy in diabetes mellitus. They have further postulated that finding of macular ischaemia on FFA can be used to predict the onset of diabetic nephropathy in diabetes mellitus. This study was undertaken to explore association between macular ischemia and nephropathy in diabetes mellitus in a rural population of Maharashtra. Aims and objectives: To explore for any correlation between ischaemic maculopathy due to diabetes and diabetic nephropathy and to find out whether ischaemic maculopathy can be used as a marker for diabetic retinopathy. Material and Methods: Fundus fluorescein angiography was done using 5ml of 20% sodium fluorescein dye to detect macular ischaemia in all the study patients. Serum creatinine, blood urea, and urine examination were done to detect nephropathy. Statistical analysis was done to find out the association between macular ischaemia and diabetic nephropathy. Observation and Results: The prevalence of nephropathy was 81% in patients with ischemic maculopathy as compared with 19% in patients without macular ischaemia. This difference was statistically significant with p <0.001. Multivariate analysis revealed that risk factors associated with diabetic nephropathy were presence of macular ischemia (odd ratio 32.9 with p <0.001), age above 65 years (odd ratio 8 with p <0.01), duration of diabetes > 20 years (odd ratio 4.1 with p <0.01), and presence of proliferative diabetic retinopathy (odd ratio 3.2 with p <0.01). Conclusion: This study found a strong correlation between ischaemic maculopathy and nephropathy in patients with diabetes mellitus. The association between ischaemic maculopathy and nephropathy remained strong even after adjusting for the confounding factors. The findings of this study suggest that macular ischaemia as seen on FFA can be used to predict the onset of nephropathy in patients with diabetes mellitus and may serve as a potential marker.